By the shore - Ryan, Denise (Australia : Weldon Owen, 2008)
These books are designed for children who are beginning to read. They feature a single, familiar topic and concept, single word labels, strong word-picture match and consistent placement of text. A series of beautifully designed, fact-filled books, richly illustrated with a wealth of accurate, full-colour illustrations, intriguing diagrams, cross sections and cutaways. The text has been carefully leveled to support children's reading development. Ideal to help all beginner readers gain confidence while they practice their reading skills enthusiastically.
D
b
b
Keywords: Shore animals and plants -- Nature